Strength of actuation singularities of corank 2 in planar 3-PRR parallel robots - Gün, Emir (My University, 2023)
Paralel robotlar, havacılık, uzay, otomotiv ve tıp gibi farklı alanlarda hareket simülatörleri, endüstriyel manipülatörler, takım tezgahları, tıbbi ve cerrahi robotlar ve haptik cihazlar gibi çeşitli şekillerde uygulamalara sahiptir. Paralel robotların bu kadar geniş bir alanda tercih edilmelerinin nedenleri konvansiyonel seri robotlara göre daha yüksek doğruluğa, daha yüksek yüksek rijitliğe, daha düşük atalete ve daha büyük yük/ ağırlık oranına sahip olmalarıdır. En büyük dezavantajları ise çalışma uzayları içerisinde yer alan aktüasyon tekillikleridir. Mekanizmanın kapalı kinematik zincir yapısında dolayı ortaya çıkan bu tekilliklere yaklaşılırken ters dinamik çözüm sonsuza ıraksar ve robotun kontrolü kaybedilir. Bu nedenlerle paralel robotların çalışma uzaylarının tamamını kullanabilmeleri için aktüasyon tekilliklerinden geçebilmeleri büyük önem taşımaktadır. Bunu gerçekleştirmek için uç işlevcinin yörüngesi, hareket denklemleri tekil konfigürasyonda tutarlı olacak şekilde planlanmalıdır. Ancak aktüasyon tekillikleri, gerçekleştirilen göreve bağlı olarak farklı mertebelere sahip olabilir ve yüksek mertebeden tekilliklerin kaldırılması için tutarlılıktan başka ek koşullar gerekir. Bu tezde, üç serbestlik dereceli düzlemsel 3-PRR paralel robotların korank 2 aktüasyon tekilliklerinin mukavemeti analiz edilmiştir. Mevzubahis robotun korank 2 aktüasyon tekilliklerinin hangi koşul altında yüksek mertebeden hale geleceği belirlenmiştir.

Parallel robots have applications in various forms like motion simulators, industrial manipulators, machine tools, medical and surgical robots, and haptic devices in different fields such as aerospace, automotive and medicine. The reasons why parallel robots are preferred in such a wide spectrum of areas are that they have higher accuracy, higher stiffness, lower inertia, and larger payload-to-weight ratio compared to conventional serial robots. Their biggest disadvantage is the presence of actuation singularities inside their workspace. When approaching these singularities, which arise due to the closed kinematic chain structure of the mechanism, the inverse dynamic solution diverges to infinity and the control of the robot is lost. For these reasons, it is of great importance for parallel robots to pass through actuation singularities so that they can use their entire workspace. To realize this, the end-effector trajectory must be planned so that the equations of motion are consistent at the singular configuration. However, actuation singularities can become of high order depending on the task being performed, and high-order singularities require additional conditions other than the consistency for being removed. In this thesis, the strength of the corank 2 actuation singularities of three-degree-of-freedom 3-PRR planar parallel robots is analyzed. It is determined under which condition the corank 2 actuation singularities of the robot under study become of high order.
Düzlemsel 3-PRR paralel robotlarda korank 2 aktüasyon tekilliklerinin mukavemeti
Keywords: Makine mühendisliği; Mechanical engineering; Paralel manipülatörler; Parallel manipulators; Robotics; Robotik; Singularity; Tekillik